Elimination of cost‐sharing and receipt of screening for colorectal and breast cancer. Issue 18 (4th June 2015) - Fedewa, Stacey A.; Goodman, Michael; Flanders, W. Dana; Han, Xuesong; Smith, Robert A.; M. Ward, Elizabeth; Doubeni, Chyke A.; Sauer, Ann Goding; Jemal, Ahmedin
<x xml:space="preserve">Abstract</x> BACKGROUND The aim of the cost‐sharing provision of the Patient Protection and Affordable Care Act (ACA) was to reduce financial barriers for preventive services, including screening for colorectal cancer (CRC) and breast cancer (BC) among privately and Medicare‐insured individuals. Whether the provision has affected CRC and BC screening prevalence is unknown. The current study investigated whether CRC and BC screening prevalence among privately and Medicare‐insured adults by socioeconomic status (SES) changed before and after the ACA. METHODS Data obtained from the National Health Interview Survey pertaining to privately and Medicare‐insured adults from 2008 (before the ACA) and 2013 (after the ACA) were used. There were 15, 786 adults aged 50 to 75 years in the CRC screening analysis and 14, 530 women aged ≥40 years in the BC screening analysis. Changes in guideline‐recommended screening between 2008 and 2013 by SES were expressed as the prevalence difference (PD) and 95% confidence interval (95% CI) adjusted for demographics, insurance, income, education, body mass index, and having a usual provider. RESULTS Overall, CRC screening prevalence increased from 57.3% to 61.2% between 2008 and 2013 (P<.001). Adjusted CRC screening prevalence during the corresponding period increased in low‐income (PD, 5.9; 95% CI, 1.8 to 10.2), least‐educated (PD, 7.2; 95% CI, 0.9 to 13.5), and Medicare‐insured (PD, 6.2; 95% CI, 1.7 to 10.7) individuals, but not in high‐income, most‐educated, and privately insured respondents. BC screening remained unchanged overall (70.5% in 2008 vs 70.2% in 2013) and in the low SES groups. CONCLUSIONS Increases in CRC screening prevalence between 2008 and 2013 were confined to respondents with low SES. These findings may in part reflect the ACA's removal of financial barriers. Cancer 2015;121:3272–3280. © 2015 American Cancer Society.